FILM DOKUMENTER DIRTY VOTE 02: BENTUK PERLAWANAN TERHADAP NARASI TUNGGAL REZIM - Mhd Ricky Ardiansyah Putra; Izuddinsyah Siregar; Ismail Jahiddin; Lode Wijk Pandapotan; Irda Yusepa (FISIP Universitas Malikussaleh, 2026)
The film Dirty Vote 02 is a critical way of talking about politics that shows disagreement with the narrative of one regime in the current Indonesian public space. The purpose of this research is to see how the film uses narrative, visual, and symbolic strategies to construct a counter-discussion about the hegemony of power. Based on Norman Fairclough's model for critical discourse analysis, the approach used is qualitative and focuses on the relationship between language, ideology, and power. The results indicate that Dirty Vote 02 film is an alternative media that seeks to revive communicative rationality (Habermas) through the dissemination of rational data and arguments and simultaneously cracks the ideological hegemony of the regime (Gramsci). This film serves as an alternative public space where people can reassess the legitimacy of power and restore critical thinking about dominant political discourse. And this film can also serve as a form of political education for the public and as a reference for analyzing symptoms or events related to politics, policy, governance, and broader societal issues, which today are mostly presented through a single discourse or narrative by various anti-mainstream media in Indonesia. Therefore, this documentary film can be used strategically as a symbolic tool to challenge the dominance of national discourse and to strengthen deliberative democracy this Indonesia.